Effect of Strained Quantum Wells of Enhanced Performance for Quantum Well Lasers in Direct Modulation - Mahdi, Mohammed Adnan (Nahrain University College of Engineering Journal, 2011)
Strained-layer quantum wells are interesting for applications in semiconductor lasers , because they allow both, a wider range of material combinations, and a certain amount of band structure and gain engineering. This layer is effected on frequency shift of the gain spectrum ,but gain increase also possible. The majoradvantages of strained quantum wells in the modulated quantum well lasers diodes are a very high modulation speed, a low frequency chirp ( - parameter) , a narrow line-width, and a low threshold carriers concentration. Strained quantum well lasers are better than the semiconductor lasers , which have a modulation band-width in upper teens and low twenties of gigahertz.